Customers’ satisfaction toward front counter services in Valuation & Property Management Department, Majlis Perbandaran Sungai Petani, Kedah (MPSPK) / Norliani Omar - Omar, Norliani (2011)
The purpose of this report was to present customers’ satisfaction towards front counter’s services in Valuation and Property Management Department, Majlis Perbandaran Sungai Petani, Kedah (MPSPK) and recommended how to improve staffs skills in provided services. The analysis was carried out over a month and I used questionnaire survey to ask the respondents. I get 100 respondents to answer the questionnaire. The findings were based on 5 Servqual dimensions that classified as tangibility, reliability, responsiveness, assurance and empathy. The findings were such as both customers’ expectation and perception in tangibility dimension are in high level with score 3.98 and 4.13 each. The Servqual gap is 0.15. Other findings were both customers’ expectation and perception in reliability dimension was in high level with score 4.04 and 3.88 each. The Servqual gap is (-0.16). The conclusion for customers’ satisfaction towards front counter’s services in Valuation and Property Management Department, (MPSPK) was such as Valuation and Property Management Department, MPSPK was not serving in the highest best skills because there were lots of negative Servqual gap rather than the positive one. Some recommendations also had been list down such as staffs need to give lots of smiles and staffs should want to offer some helps